The 100 most influential manuscripts in colorectal cancer: A bibliometric analysis. Issue 6 (December 2016) - Wrafter, Paula F.; Connelly, Tara M.; Khan, Jody; Devane, Liam; Kelly, John; Joyce, William P.
Abstract: Purpose: Bibliometric analysis highlights the key topics and studies which have led to the current understanding and treatment of a disease of interest. In this original article we analyze the 100 most cited manuscripts in the field of colorectal cancer (CRC). Materials and methods: The Thomson Reuters Web of Science database with the search terms 'colorectal cancer, ' 'colorectal cancer surgery, ' 'colon cancer, ' 'rectal cancer, ' 'colorectal carcinoma, ' 'colon carcinoma, ' 'rectal carcinoma' and/or 'colonoscopy' was used to identify the manuscripts for the study. Only full length manuscripts were included. The 100 most cited papers were identified and further analyzed by topic, journal, author, year and institution. The journals' 5 year impact factor and Eigenfactor scores were recorded. Results: 146, 833 eligible papers were returned. Within the top 100 cited manuscripts, the most studied topic was genetics in CRC (n = 41), followed by chemotherapy (n = 20) and surgical management (n = 7). The most cited paper authored by Fearon et al. (7850 citations) focused on genetic models of tumorgenesis. The NEJM published the highest number of papers (n = 23 with 42, 576 citations). The country and year with the greatest number of publications were the USA (n = 62) and 2004 (n = 13) respectively. Conclusion: The most cited manuscripts highlighted in the current work describe the genetic, immunologic, basic science and surgical techniques that have resulted in the current understanding and treatment of CRC. The majority of these works were published in high impact journals and have been cited at least 900 times each reflecting their quality and influence. This work provides a reference of what could be considered as the most influential papers in CRC and serves as a reference for researchers and clinicians as to what makes a 'citable' paper.